PENGGUNAAN CANVA DALAM PEMBELAJARAN BAHASA JEPANG DI SMA NEGERI 1 CANDUNG - Yusra; Supratman Zakir (CV. ALIM'SPUBLISHING, 2024)
Abstract. Abstract. This journal discusses Canva, an online platform that provides many templates and images for creating presentations, infographics and documents. In learning Japanese at SMA Negeri 1 Candung, Canva can be used as a tool to develop student creativity and combine Japanese language knowledge with technology. Using Canva in learning Japanese at SMA Negeri 1 Candung has several benefits, namely: Helping students develop creativity. Canva allows students to create interesting and unique presentations, infographics and documents. Students can use images, fonts and themes that are appropriate to the material being studied. Canva can be used to create posters, flyers and brochures that convey information in Japanese. Canva allows students to learn graphic and design techniques. Students can practice technical competence in using the Canva application to create professional and attractive presentations, infographics and documents. To work collaboratively in practicing Japanese language competence. Students can train collaborative competencies in creating presentations, infographics and documents that convey information in Japanese together, train digital literacy competencies in using the Canva application to conduct research or convey information in Japanese digitally. Using Canva in learning Japanese in high school can be done online or offline, depending on the student's needs and conditions.